2017
DOI: 10.1007/s10552-017-0973-0
|View full text |Cite
|
Sign up to set email alerts
|

Examining HPV- and HPV vaccine-related cognitions and acceptability among US-born and immigrant hispanics and US-born and immigrant non-Hispanic Blacks: a preliminary catchment area study

Abstract: Group disparities in HPV vaccine cognitions emerged, but they all had notable HPV vaccine acceptability (safety and efficacy) barriers. HPV vaccine safety and efficacy were highly unfavorable in US-born AA. The HPV vaccine safety concerns are demonstrated with only 31-54% reporting that the "HPV vaccine is safe"-potentially increasing their risk of HPV vaccine negation. With regards to HPV vaccine efficacy, only 40-63% of this study population endorsed HPV vaccine efficacy. Additionally, immigrants reported gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 15 publications
0
8
0
2
Order By: Relevance
“…A quantitative study conducted in Southern California compared knowledge and acceptability between US-born African Americans and African immigrants, and between US-born Latinas and Latina immigrants. African and South American immigrants were less likely to know where they can get/refer for HPV vaccine and less likely to have heard about HPV vaccine than South Americans and US-born Africans [43]. Similarly, a study in Denmark found that refugee girls, mainly from Muslim countries, had significantly lower HPV immunization uptake compared to Danish born girls, indicating that refugee girls may face challenges to access and use of immunization services [44].…”
Section: Discussionmentioning
confidence: 99%
“…A quantitative study conducted in Southern California compared knowledge and acceptability between US-born African Americans and African immigrants, and between US-born Latinas and Latina immigrants. African and South American immigrants were less likely to know where they can get/refer for HPV vaccine and less likely to have heard about HPV vaccine than South Americans and US-born Africans [43]. Similarly, a study in Denmark found that refugee girls, mainly from Muslim countries, had significantly lower HPV immunization uptake compared to Danish born girls, indicating that refugee girls may face challenges to access and use of immunization services [44].…”
Section: Discussionmentioning
confidence: 99%
“…However, pockets of low HPV vaccine coverage persist, including in immigrant and racial/ethnic minority communities in Los Angeles (Los Angeles County Department of Public Health, 2018 ). Barriers to adolescent HPV vaccination previously identified by racial/ethnic minority parents include perceived high financial cost, limited access to in-language vaccine information and understanding of medical terms, lack of provider recommendation, and low HPV vaccine knowledge (Aragones et al, 2016 ; Ashing et al, 2017 ; Glenn et al, 2015a , 2015b ; Kornfeld et al, 2013 ; Roncancio et al, 2017 ; Victory et al, 2019 ; Vu et al, 2020 ; Warner et al, 2015 ). Less is understood about the role of vaccine hesitancy in racial/ethnicity communities and the impact on HPV vaccine uptake, particularly in recent years when general vaccine confidence has declined overall in the US and internationally.…”
Section: Introductionmentioning
confidence: 99%
“…HPV vaccine knowledge among parents continues to be an important predictor of HPV vaccine initiation [ 7 ]. Despite increasing numbers of immigrants in the U.S. [ 8 ], assessments of HPV vaccine knowledge among immigrants parents have primarily focused on Latinx/Hispanic groups, parents of low socioeconomic status, and other medically underserved populations [ 9 , 10 ]. Studies have shown that immigrant parents often have little knowledge of the HPV vaccine and vaccine decision-making is often influenced by cultural norms and sexual misconceptions [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%